PENERAPAN ALGORITMA C4.5 DALAM PENENTUAN PENERIMA BONUS TAHUNAN PADA KARYAWAN PT WAEN INDONESIA - Khe Ben; Elisa, Erlin (Computer Science and Industrial Engineering, 2022)
PT Waen Indonesia is a professional company specializing in plastic production that provides goods such as LDPE, HDPE, PET, ABS, PS/HIPS, GPPS, PC, PMMA, Silicon, POM, PPS, PBT, and so on. As the years pass, employees at PT Waen Indonesia are often dissatisfied with the annual bonuses they receive, so this problem causes a lack of employee performance, employee discipline, and employee loyalty to PT Waen Indonesia. With a big motto in the global market, PT Waen Indonesia, of course, must have quality human resources. One of them is in improving employee performance, employee discipline, and employee loyalty to PT Waen Indonesia, then every year the leadership of PT Waen Indonesia gives bonuses to employees. PT Waen Indonesia has quite a lot of employees, so with the number of employees to be analyzed, a company leader must work hard in analyzing which employees are eligible to receive this annual bonus. The results of the decision tree that have been tested produce the highest gain value which is an important factor because it has a large enough influence in determining the annual bonus for PT Waen Indonesia employees, these factors come from the attributes of years of service, targets, and attendance.